2009
DOI: 10.1007/s00402-009-1015-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of platelet-rich plasma on the anterior fusion in spinal injuries: a qualitative and quantitative analysis using computer tomography

Abstract: The additional application of autologous PRP involves very little risk for the patients. The study implies that the use of PRP provides a faster fusion and higher density values within the fusion mass. A clear advancement in spinal fusion in terms of a clinical benefit remains questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 29 publications
1
54
0
1
Order By: Relevance
“…Recently there have been conflicting reports about the effect of PRP plasma, and there is no consensus regarding the role of PRP in bone regeneration: there are multiple favorable results of PRP regarding the improvement of proliferation of MSC in vitro and in vivo after ectopic implantation, but also in animal models with critical-size bone defects [Kasten et al, 2008b;Bi et al, 2010;Hakimi et al, 2010;Hartmann et al, 2010;Jungbluth et al, 2010;Niemeyer et al, 2010;Bae et al, 2011;Liu et al, 2011]. However, there is also a relevant number of studies reporting no or minimal effects of PRP on bone formation [Li et al, 2004;Roldan et al, 2004;Plachokova et al, 2007;Thor et al, 2007;Vasconcelos Gurgel et al, 2007;You et al, 2007;Miloro et al, 2010;Kazakos et al, 2011].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there have been conflicting reports about the effect of PRP plasma, and there is no consensus regarding the role of PRP in bone regeneration: there are multiple favorable results of PRP regarding the improvement of proliferation of MSC in vitro and in vivo after ectopic implantation, but also in animal models with critical-size bone defects [Kasten et al, 2008b;Bi et al, 2010;Hakimi et al, 2010;Hartmann et al, 2010;Jungbluth et al, 2010;Niemeyer et al, 2010;Bae et al, 2011;Liu et al, 2011]. However, there is also a relevant number of studies reporting no or minimal effects of PRP on bone formation [Li et al, 2004;Roldan et al, 2004;Plachokova et al, 2007;Thor et al, 2007;Vasconcelos Gurgel et al, 2007;You et al, 2007;Miloro et al, 2010;Kazakos et al, 2011].…”
mentioning
confidence: 99%
“…Regarding its clinical use in maxillofacial surgery, a recent metaanalysis indicated that there was sufficient evidence to support the use of PRP for bone formation on a sinus bone graft, whereas there was no significant effect on the implant survival and bone-to-implant contact [Bae et al, 2011]. In orthopedic surgery, some authors report positive outcomes in leg lengthening procedures and spinal fusions [Bi et al, 2010;Hartmann et al, 2010]. In summary, the role of PRP remains controversial.…”
mentioning
confidence: 99%
“…Its use in intersomatic arthrodesis shows similar results between autograft or allograft plus autologous platelet concentrate [14]. When the analysis of the cage filled with autograft (with or without autologous platelet concentrate) was made by CT, it was observed a quicker fusion in those patients with autologous platelet concentrate added, although the result, at the end of the follow-up, was the same [12]. It is true some authors emphasize on its goodness for lumbar arthrodesis [4,6] but our results agree with those from literature and we can claim, as a rule, that we get less fusion rates when adding autologous platelet concentrate to autograft or autograft plus TCP/HA [5,17,24,26,30].…”
Section: Discussionmentioning
confidence: 87%
“…In particular, platelets play an active role by producing several pro-and anti-inflammatory mediators, including cytokines (TGF-~, IL-l~, CD40L) and chemokines (CXCL-l, -4, -5, -7, -8, -12 CXCL-4Ll, CCl-2, -3, -5), being themselves regulated by the inflammatory response through their chemokine receptors (CCR-l, 3,4, CXCR-4) (71). Dependently from this evidence, spine fusion techniques (74), as well as the whole set of orthopaedic surgeries (75), have been implemented with the use of the platelet-rich plasma (PRP) to improve the healing based on the pro-reparative properties of the platelet content (76). After the activation platelets degranulate releasing the contents of their granules consisting of inflammatory and growth factors (platelet-derived growth factor (PDGF), TGF-a and~, epidermal growth factor (EGF), fibroblast growth factor (FGF) -2, insulin-like growth factor (IGF) and vascular endothelial growth factor (VEGF) (77,78).…”
Section: The Importance Ofcytokines In Wound Healingmentioning
confidence: 99%